SOME FEATURES OF CHEMICAL ELEMENT ACCUMULATION IN PLANTS - G. R. Valeeva (Ûg Rossii: Èkologiâ, Razvitie, 2014)
When young sterlet is suffering from tympanism, biochemical and pathophysiological disorders are observed; the activity of malate dehydrogenase and succinate dehydrogenase lowers in the fish liver and muscles, while the activity of lactate dehydrogenase in-creases. Such disorders are accompanied by changes in the level and balance of ω-3 and ω-6 fatty acids towards decrease in ω-3 fatty acids.